Effect Of Cutting Speed On The Carbide Cutting Tool In Milling Inconel 718 Alloy - Abdul Hadi, Musfirah; A Ghani, Jaharah; Che Haron, Che Hassan; Kasim, Mohd Shahir (Cambridge University Press, 2016)
Tribology is a phenomenon concerning the relative motion between at least two amalgamating surfaces. In the machining process, surface roughness is the most important element for studying this occurrence, which contributes to the evaluation of part quality. This paper will provide detailed analysis for better understanding of tribological during the machining process of Inconel 718 alloy using a multi-layer TiAlN/AlCrN-coated carbide ball end inserted in dry cutting condition. The analysis focused on the relationship of tool wear with cutting temperature, cutting force, and surface integrity. Results found that the cutting temperature increased around 7.5% and surface roughness of machined surface improved about 10.3% when the cutting speed increased. Flaking at the rake face and notching at the flank face were determined as the main tool failures during milling Inconel 718. Furthermore, high friction between the tool–workpiece interfaces during machining was due to the build-up edge (BUE) formation that causes an alteration in microstructure at machine surface.